Branding a Memorable: Case Study on Residivist Streetwear Bandung - Safiratul Zakiyah; Yulianti Yulianti (MediaTor (Jurnal Komunikasi), 2020)
The trust issue occurred toward the former prisoners made it difficult for them to return to society. Based on this issue, an effort was made to counter the stereotypes developed in the community. Unlike other clothing businesses, Residivist Streetwear has a unique concept, which manifested in the design of its products. Residivist Streetwear uses the idea of "Prison Culture" in every designs. Moreover, 99% of its employees are recidivists. With the stigma and discrimination that the ex-prisoners received, it is not easy for Residivist Streetwear to make its brand known and accepted by the community. This article aims to find and to analyze Residivist Streetwear’s branding strategies. The method used in this study is a qualitative method with a case study approach. Based on the research, it was found that Residivist Streetwear’s branding strategies included, (1) increasing brand appeal through product maker’s background, brand name, product hang tag, and the use of product design with the "Prison Culture” concept; (2) communicating brands through endorsement, sales promotion, social media, television, and various events and programs of the Anugerah Insan Residivist Foundation; (3) the use of product design with the concept of “Prison Culture” is a hallmark of Residivist Streetwear in changing the stigma aimed by the community to ex-convicts.